Exploring family business succession in an integrative familiness transmission of capital model: a South African study. (6th October 2010) - Venter, W.P.; Kruger, S.; Urban, B.
This study investigates how familiness could ensure successful transition of family-capital, by modelling the different evolutionary stages through which the transmission of capital takes place. The study is contextualised in South Africa, where more than half of listed businesses are family firms. The nurturing of family businesses in South Africa has been cited as an important aspect in the stimulation of the economy as well as the creation of enduring social stability. Results are reported from interviewing (n = 66) family executives, identifying salient variables influencing channels which depict important pathways in which reciprocal relationships are acted out. Resonating with previous studies the present study finds that successors observe a rich array of variables which influence transmission channels. This study makes a modest contribution to the literature of family business by conceptualising a model that explains the developmental stages of each generation succession. Even more so by interrogating factors conceptualised from a predominantly Western perspective, the study is a starting point for research investigating familiness in a developing country context.